The PENGARUH PEKERJA SEKTOR INFORMAL TERHADAP PENERIMAAN PERPAJAKAN DAN PENERIMAAN PAJAK PENGHASILAN - Robby Alexander Sirait (Jurnal Budget : Isu dan Masalah Keuangan Negara, 2023)
The amount of informal workers is one of the factors that affected the tax revenue and income tax revenue. This research examines the effect of informal workers on tax revenues and income tax revenue by analyzing a panel data set of thirty-three provinces from 2016 to 2020. Using the Common Effect Model, our findings show that informal workers negatively affect tax and income tax revenue. Moreover, this research also finds that Gross Domestic Regional Product (GDRP) positively affects tax and income tax revenue. Based on research findings, we suggest the government formalize the informal workers and increase the growth of GDRP. Besides that, the government must also increase the tax knowledge of informal workers and improve tax services and tax audits for informal workers as taxpayers.